Digital Quantification of the Enzyme-Linked Immunospot (ELISPOT). (November 1998) - Vaquerano, J.E.; Peng, M.; Chang, J.W.C.; Zhou, Y.-M.; Leong, S.P.L.
Enzyme-linked immunospot (ELISPOT) is a sensitive technique for the detection of cytokines released by immune cells. The technique is well established and correlates closely with the enzyme-linked immunosorbent assay (ELISA) technique. Here, we introduce an integrated imaging-analysis system to quantitate the spots formed by the ELISPOT assay. The spots can be easily counted when the background is clear and the spots are few. However, when the number of spots increases to >100, this task becomes challenging and time-consuming. To minimize time and standardize the counting procedure, we have used a digital camera linked to a computer system for reading the plates. In general, the computer is able to count more spots and has a smaller standard deviation when compared with the manual microscopic count. This integrated system is commercially available, and we believe that this method is objective, timesaving and consistent in routine ELISPOT assay counting, especially when numerous spots are present.